Integrasi Kecerdasan Buatan dalam Taktik Pemasaran : Dampaknya terhadap Pengembangan Keterampilan Pemasaran Generasi Baru - Zuhrinal M. Nawawi; Elvira Andriyani (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This research uses a qualitative method to explore the integration of Artificial Intelligence (AI) in marketing tactics and its impact on the development of marketing skills among the new generation. The main focus is on the use of AI in analyzing consumer behavior, content personalization, campaign automation, and data-driven decision-making. The findings reveal that AI not only enhances operational efficiency but also drives a transformation in the skill sets required by modern marketers, such as data analysis capabilities, technological literacy, and adaptability to intelligent systems. Through in-depth interviews with marketing practitioners and digital document analysis, it was discovered that the new generation of marketers is required to develop more complex digital competencies and engage in multidisciplinary collaboration. Furthermore, adaptation to technological change becomes a key factor in the success of AI-based marketing strategies. The integration of artificial intelligence in marketing practices not only reshapes work patterns but also creates new demands for continuous training and marketing education. Therefore, this research emphasizes the importance of collaboration between educational institutions, industry, and technology developers to create a competitive AI-based marketing ecosystem.